PHYSICAL PROPERTIES OF WOUND HEALING GEL OF ETHANOLIC EXTRACT OF BINAHONG (Anredera cordifolia (Ten) Steenis) DURING STORAGE. - Sri Hartati Yuliani; Achmad Fudholi; Suwijiyo Pramono; Marchaban . (Indonesian Journal of Pharmacy, 2012)
Binahong  (Anredera  cordifolia (Ten)  Steenis)  has  been used  as  wound  healing  in  traditional  Indonesian  medicine.  The developing of the dosage forms using the formulation technology approach  has  been  done.  The  aim  of  this  study  was  to  examine the  physical  properties  of  the  wound  healing  gel  of  ethanolic extract of binahong during storage. The factorial design method 3 factors  and  2  levels  was  employed  to  achieve  this  study.  The three  factors  used  in this  study  were Carbopol, CMC-Na  and Caalginate  with  low  and  high  level  for  each  factor.  The  physical properties  of  the  wound  healing  gel  of  ethanolic  extract  of binahong was evaluated on day 1, 30, 60 and 90 for viscosity and bioadhesion  study.   The  result  showed  that  CMC-Na  and  Caalginate  increased  the  alteration  of  physical  properties  of  wound healing  gel  of  ethanolic  extract  of  binahong  during  storage.  The carbopol  maintained  the  physical  properties  of  the  gel  during storage.Key words: bioadhesion, binahong, viscosity, wound healing gel.